What is Life? - Witzany, Guenther (Frontiers in Astronomy and Space Sciences, 2020)
In searching for life in extraterrestrial space, it is essential to act based on an unequivocal definition of life. In the 20th century, life was defined as cells that self-replicate, metabolize and are open for mutations, without which genetic information would remain unchangeable and evolution would be impossible. Current definitions of life derive from statistical mechanics, physics and chemistry of the 20th century in which life is considered to function machine-like, ignoring a central role of communication. Recent observations show that context dependent meaningful communication and network formation (and control) are central to all life forms. Evolutionary relevant new nucleotide sequences now appear to have originated from social agents such as viruses, their parasitic relatives and related RNA-networks, not from errors. By applying the known features of natural languages and communication, a new 21st century definition of life can be reached in which communicative interactions are central to all processes of life. A new definition of life must integrate the current empirical knowledge about interactions between cells, viruses, and RNA-networks to provide a better explanatory power than the 20th-century narrative.